An injectable superior depot of Telratolimod inhibits post-surgical tumor recurrence and distant metastases. (15th March 2022) - Liu, Yubo; Li, Chang; Xia, Hong; Bi, Jiahao; Guan, Rou; Du, Xiaoxiao; Zhang, Haotian; He, Zhonggui; Wang, Yongjun; Liu, Hongzhuo
Abstract: The clinical success of Toll-like receptor (TLR) agonists is based on their capacity to efficiently mobilize both innate and adaptive immunity. However, rapid distribution of TLR agonists into the systemic circulation may result in systemic cytokine storms. Telratolimod (Tel) is a TLR 7/8 agonist whose structure has a hydrophobic long chain that helps to prolong its release. Despite this, the phase I study of Tel showed cytokine release syndromes in 3/35 patients. Herein, we designed an injectable phase transition gel (PGE) that served as a superior drug depot for fatty acid-modified drugs. PGE further minimized the systemic drug exposure of Tel and the possible cytokine storms. In vivo studies demonstrated that Tel@PGE facilitated the recruitment of effector CD8 + T lymphocytes (T cells) and the polarization of myeloid-derived suppressor cells (MDSCs) and immunosuppressive M2-like macrophages to tumoricidal antigen-presenting cells. The reshaping of the tumor microenvironment (TME) by Tel@PGE elicited systematic immune responses to significantly prevent B16F10 or 4T-1 tumor postoperative recurrence and metastasis. Therefore, this platform of Tel is expected to provide a clinically available option for effective postoperative combined therapy. Statement of significance: A series of prodrugs or conjugates containing hydrophobic blocks were designed to achieve sustained release at the injection site by reducing the water solubility. However, this strategy sometimes failed short of expectations. Thus, we constructed a biocompatible and biodegradable injectable phase transition gel (PGE) with superior release properties that can be injected subcutaneously into the surgery site. In the long-lasting treatment, the melanoma and breast cancer immunotherapeutic effect significantly enhanced and the risk of cancer metastasis and relapse was reduced. Crucially, for some immune agonists, a superior release control can significantly reduce adverse effects which was decisive for the availability of the drugs. Graphical abstract: Image, graphical abstract